Feeding – Cleaning Trade-Off: Manta Ray “Decision-Making” as a Conservation Tool - Barr, Yotam; Abelson, Avigdor (Frontiers in Marine Science, 2019)
Identifying critical aggregation sites and behavioral patterns of imperiled species contributes to filling knowledge gaps essential for their conservation. Manta rays present a prominent example of such species, the populations of which are declining globally due to directed fishery, by-catch, and other anthropogenic stressors. Our goal was to explore manta ray aggregation sites in the Philippines in order to determine the factors governing the mantas’ visits – a knowledge gap essential to understand manta ecology, facilitate ecosystem-based fishery management, and promote sustainable manta-based ecotourism. Diving surveys, environmental conditions assessment, and autonomous cameras were employed to study manta behavior and visit patterns to a cleaning station cluster on a commonly fished seamount, visited by both Mobula birostris and Mobula alfredi. Our findings reveal several environmental conditions (e.g. sea state, moon illumination, and flow) that serve as predictors of manta presence/absence at the site. We suggest that these conditions affect both the behavior of the manta’s food (i.e. the spatial distribution of plankton) and the cleaner wrasses’ cleaning effectiveness, which consequently influence manta activity. The findings suggest a trade-off between cleaning and foraging: i.e. mantas tend to visit the cleaning stations when environmental conditions are less favorable for foraging but suitable for effective cleaning; while being absent from the cleaning stations when environmental conditions form plankton aggregates, ideal for efficient feeding. This study sheds light on manta behavior and habitat use on dynamic small spatio-temporal scales (i.e. hundreds of meters to a few kilometers, hours to days), and may be applied in the planning of marine protected areas and in fishery management, as well as contribute to enhancing sustainable exploitation of manta rays by local stakeholders, such as ecotourism operators.